TECHNOLOGICAL BASES OF HARVESTING AND EQUIPMENT FOR LUCERNE SEEDS CLEANINGS - A. Lee (Сельскохозяйственные машины и технологии)
For development of technological bases of harvesting and equipment of cleaning of lucerne seeds it is necessary to take as a basis the  agrotechnical requirements imposed to seeds during their  harvesting, processing (rub threshing) and cleaning (sorting).  lucerne seeds harvesting has to take place in the period of their wax  ripeness. When maturing 70-80 percent of seeds in beans and seeds humidity of 60-65 percent plants are mowed in windrows and  dried till humidity of 14-15 percent. The humidity of beans when processing (rub threshing) should not exceed 14 percent. The technology with stationary processing of a harvest (heap) providing  the minimum losses of seeds is effective and most perspective. The authors offered the modernized technology of seeds cleaning  with use the MB-2.5A thresher winnower, the modernized clover huller K-0.5M and the dielectric seed cleaning device. Seeds heap after processing by MB-2.5A consists of the following components:  seeds – 35-44 percent, organic inclusions (leaves, stalks, seeds of  foreign cultures) – 49-67 percent, mineral inclusions (dust, clay,  small stones) – 1-2 percent. The modernized clover huller K-0.5M  provides: completeness of rub threshing – 98.5 percent; purity of  seeds – 85.7 percent; damage of seeds – 1.8 percent; losses of  seeds – 1.4 percent; heap productivity – 0.5-0.6 t/h and losses reduction by 2-2.5 times. Dielectric apparatus separates lucerne seeds from quarantine  inclusions with a triboelectric method. The  efficiency of seeds cleaning for the first fraction was 53.1 percent,  for the second one – 38.5 percent and for the third one – 11.9  percent. The cost of lucerne seeds cleaning decreases by 1.5 times  due to the modernized technology.